ANALISIS PENGARUH PROFITABILITAS, LEVERAGE, CORPORATE SOCIAL RESPONSIBILITY, KEPEMILIKAN INSTITUSIONAL DAN KUALITAS AUDIT TERHADAP TAX AVOIDANCE PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA PERIODE 2016-2019 - Wesley Andri Simanjuntak (JURNAL MANAJEMEN, 2020)
This research is a quantitative research that aims to analyze the effect of profitability, leverage, Corporate Social Responsibility, institutional ownership and audit quality on tax avoidance. Object of the study are manufacture companies listed on the Indonesia Stock Exchange in period of 2016-2019. The sample of this study were 40 companies selected with certain criteria. The analysis tool used was multiple linear regression with the t-test and coefficient of determination using the SPSS version 25 program with a significance level of 5%(0.05). The results of this study indicate that: (1) profitability had significant influence on tax avoidance, (2) leverage has no significant influence on tax avoidance, (3) Corporate Social Responsibility has no significant influence on tax avoidance, (4) institusional ownership has no significant influence on tax avoidance, (5) audit quality has no significant influence on tax avoidance.